Peran JPN Kejaksaan Badung Dalam Perwalian Anak Yatim Piatu Berdasarkan Peraturan Kejaksaan Nomor 7 Tahun 2021 - Juliani, Kadek Eni; Budiana, I Nyoman; Prasada, Dewa Krisna; Rusmana, I Putu Edi (Consensus : Jurnal Ilmu Hukum, 2025)
This study aims to analyze and elaborate on the operational mechanisms and challenges faced by the State Attorney (JPN) of the Badung District Attorney’s Office in executing the guardianship function for orphans, based on the mandate of the Attorney General’s Regulation of the Republic of Indonesia Number 7 of 2021 concerning Guidelines for the Implementation of Other Legal Actions (THL). The method employed is normatif through a literature review. The findings indicate that the JPN has fulfilled its role, starting from asset identification, inventory, to accountability reporting, which legally provides certainty and protection over the children's assets. However, implementation faces significant constraints in cross-sectoral coordination with the Court and local government agencies, as well as challenges in managing complex assets. Therefore, it is recommended to enhance the JPN's human resource capacity in financial asset management and improve internal procedures through the development of detailed Standard Operating Procedures (SOPs), to realize a more efficient, transparent, and fully child-best-interest-oriented guardianship execution.